Myths, ıslamic view, and science concepts: The constructed education and knowledge of solar eclipse in ındonesia - Harıstıanı, Nuria; Aryantı, Tutin; Nandıyanto, Asep Bayu Dani; Sofıanı, Desri (Journal of Turkish Science Education, 2024)
This study examines Indonesian students’ constructed knowledge of solar eclipse. It investigated the embraced myths, religious view—particularly that of Islam, and science concept that build students’ comprehension of the solar eclipse. A survey was done in Bandung (Indonesia), where the solar eclipse took place on March 9, 2016, to 529 students (categorized on age and educational level) and 67 lecturers, and interviews with college students. Results showed that students’ belief on mystical stories decreased along with the older of the age and the higher of their educational level. Furthermore, most lecturers have good understanding about the solar-eclipse rituals and myths, in which this supports the student understanding. The interviews revealed that while some myth-based practices were still embraced, students’ understanding of the solar eclipse is still dominated by the science concept and the Islamic religious views that they have learned since their elementary education. The literature showed that two of eleven solar-eclipse rituals and myths in Indonesia are relevant to the science and Islamic views. Therefore, the myth, science concept, and Islamic view on the solar eclipse phenomena should be delivered since the elementary education. This study recommends teachers to integrate science with reallife context to enrich students’ understanding while clarifying false information.